A SYSTEMATIC LITERATURE REVIEW ON: STEWARDSHIP THEORY (2020 – 2024) - Devica Amanda; Sambas Ade Kesuma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study reviews the development of research related to Stewardship Theory published in the 2020–2024 period using a Systematic Literature Review (SLR) approach with PRISMA guidelines. Stewardship Theory emphasizes the behavior of managers as stewards who act in the interests of owners or organizations based on the values ​​of trust, moral responsibility, and loyalty. Data were obtained from the Scopus database, resulting in 21 articles that met the research criteria. The review results indicate that this theory is widely applied in the context of public organizations, family businesses, and risk management, with a focus on ethical leadership, internal audit systems, and organizational transparency. Conceptually, this study strengthens the understanding that stewardship values ​​such as trust, social responsibility, and organizational ethics have a crucial role in driving sustainable governance and long-term performance. This study also provides direction for further research related to the application of Stewardship Theory in modern governance and management.